THE EFFECT OF 1,1-DICHLORO-2,2-BIS (P-CHLOROPHENYL) ETHANE (DDD OR TDE) ON THE ADRENAL CORTEX OF G0ATS - HATZIOLOS, B.C. (Journal of the Hellenic Veterinary Medical Society, 1959)
NO ABSTRACT AVAILABLE